2020
DOI: 10.17582/journal.jahp/2020/9.s1.61.68
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Clostridium perfringens in Retail Meat and Meat Products with Some Decontamination Trials by some Essential Oils

Abstract: Meat is a valuable contribution to diets because of its high nutritional values. Clostridium perfringens is a commensal inhabitant of animals and human intestinal tract as well as a common foodborne pathogen associated with food poisoning. The present study was carried out to investigate the prevalence of C. perfringens in meat and its products at Zagazig city, Sharkia Governorate, Egypt. In addition, toxin genes, antimicrobial susceptibility testing and biofilm formation of C. perfringens strains isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The bacterial colonies were used to prepare slide and were stained by Grams' staining to know the characteristics of bacteria. Biochemical assessments were performed to determine the species of bacterial isolates on the basis of their biochemical characteristics (El-Bayomi et al, 2020;Musawa et al, 2021). Then antibiotic sensitivity test was performed to assess the sensitivity of pathogenic organism against eight different antimicrobials i.e., norfloxacin, tetracycline, neomycin, gentamicin, ampicillin, streptomycin, ciprofloxacin and erythromycin.…”
Section: Bacteriological Examinationmentioning
confidence: 99%
“…The bacterial colonies were used to prepare slide and were stained by Grams' staining to know the characteristics of bacteria. Biochemical assessments were performed to determine the species of bacterial isolates on the basis of their biochemical characteristics (El-Bayomi et al, 2020;Musawa et al, 2021). Then antibiotic sensitivity test was performed to assess the sensitivity of pathogenic organism against eight different antimicrobials i.e., norfloxacin, tetracycline, neomycin, gentamicin, ampicillin, streptomycin, ciprofloxacin and erythromycin.…”
Section: Bacteriological Examinationmentioning
confidence: 99%
“…Abd El-Tawab et al (2017) reported that the sulfamethoxazoletrimethoprim combination showed moderate efficacy against C. perfringens isolates. El-Bayomi et al (2020) demonstrated that all C. perfringens isolates examined were resistant to oxytetracycline, while 90% of the isolates were resistant to amoxicillin and 80% to ampicillin.…”
Section: Discussionmentioning
confidence: 99%
“…Definite toxin types produce intestinal disease in numerous species of animals (Nazki et al, 2017). A study reported the 14.5% occurrence of C. perfringens in food samples and recommended that it is important to ensure product protection mainly when it is to be consumed by newborns and elderly people (El-Bayomi et al, 2020). A previous study conducted in Punjab, Pakistan showed 64 and 37% prevalence of C. perfringens in diseased and healthy animals respectively (Mohiuddin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%